Evaluation of commonly used fertilizers, fish and poultry feeds as potential sources of heavy metals contamination in food (Asian-Australasian Journal of Food Safety and Security, 2017)
An experiment was conducted at the Department of Agricultural Chemistry, BAU to assess the heavy metal status in different feed and fertilizer samples collected from Sadar and Trisal upazilas of Mymensingh district. The feed samples included poultry and fish feeds, whereas, fertilizer samples included DAP, TSP, MOP, gypsum and zinc sulphate (ZnSO4). AAS analysis of Cd, Cr and Pb showed variable levels of contamination in the fertilizer and feed samples. In case of feed samples, Cd, and Pb contents in fish feed collected from Sadar upazila was 0.159 and 3.581 mg kg-1, respectively and that of Trisal upazila was 0.441 and 153.824 mg kg-1, respectively. The content of Cd was 0.008 mg kg-1 in poultry feed but in fish feed it was 0.441 mg kg-1. The Cr content in both poultry and fish feeds collected from Sadar and Trisal upazilas were below the detection level. In general, heavy metals contaminations were higher in different fish feed samples compared to that of poultry feed samples, especially in samples from Trisal upazila.The Cd contents in DAP, TSP, MoP, gypsum and ZnSO4 collected from Sadar upazila were 1.560, 14.749, 0.137, 0.906 and 10.312 mg kg-1, respectively, and that of Trisal upazila were 1.780, 15.662, 3.988, 1.180 and 3.165 mg kg-1, respectively. The Cr contents in DAP, TSP, MoP, gypsum and ZnSO4 collected from Sadar upazila were 60.392, 206.667, 15.882, 24.314 and 11.373 mg kg-1, respectively. Whereas, mean Cr concentrations DAP, TSP, MoP and gypsum from Trisal upazila were 54.118, 168.431, 16.078 and 26.863 mgkg-1, respectively. However, in ZnSO4Cr was below the detection limit. Again, Pb contents in DAP, TSP, MoP, Gypsum and ZnSO4 collected from Sadar upazila were 12.633, 45.729, 33.586, 13.319 and 30.014 mg kg-1, respectively, and that of Trisal upazila were 4.062, 46.919, 101.205, 21.681 and 6.676 mg kg-1, respectively. In general, heavy metal contamination levels in different fertilizer samples collected from Mymensingh Sadar were higher compared to that of Trisal upazila. The results showed that despite the close proximity of the market locations, heavy metal contents may vary in fertilizer and feed samples indicating various supply chains of these essential inputs are in place and calls for greater degree of quality monitoring from the government point of view.Asian Australas. J. Food Saf. Secur. 2017, 1 (1), 74-81